Tanggung Jawab Hukum atas Informasi Individu Pemilih pada Pemilu 2024 - Mukhammad, Bahir (Neolectura, 2024)
The proper to individual security could be a ensure of sacred rights contained in Article 28 F of the 1945 Structure which states that everybody has the right to urge information to create the individual and social environment, as well as the proper to look for, get, have, store, prepare, and pass on data utilizing all sorts of accessible channels. Individual Information in the form of direct or indirect data can be managed by individuals, public bodies, and international organizations with the permission of the proprietor of the individual information. The General Election Commission as the public body organizing the general election processes Individual Information in order to create election digitization starting from the pre-election stage, election to the post-election stage. The digitization process itself is accompanied by technological risks such as the collection of Individual Information by unauthorized parties through the database of election organizers. The irresponsible use of Individual Information has consequences for legal liability. How far is the legal responsibility for voters' Individual Information and how effective is the implementation of the Individual Information Protection Law on voter data and which Individual Information protection patterns need to be developed. This research focuses on the analysis of legal liability and the ideal concept of providing compensation for victims of Individual Information misuse is a juridical-normative study. The analysis of legal materials is carried out qualitatively-prescriptively, which is oriented to answering legal problems that have been raised with a regulatory and conceptual approach. The purpose of this research is to examine who is responsible for Individual Information and evaluate how well voter Individual Information security is being implemented during general elections. It is expected that the findings of this consider will progress our understanding of the election law and inspire more research about it.